Implementasi Nilai-Nilai Dakwah Ekologis dalam Program Pengembangan Kampung Wisata Matras Kelurahan Sinar Baru Kabupaten Bangka - Ichsan Habibi (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2017)
Positive contributions and trends in the tourism sector on Bangka Island, especially in the Matras Tourism Village, need to receive appreciation and support from all stakeholders through the management of environmentally friendly and sustainable tourist objects / attractions. To realize this mission, it is necessary to do ecological propaganda (religious values ​​originating from the Qur'an and Hadith) that are in accordance with the sociocultural characteristics of society. This issue is the subject of discussion in this study, especially regarding the values ​​of ecological preaching implemented in the development program of the Mattress Tourism Village. For this reason, a descriptive-qualitative study was conducted by collecting purposive-snowball data from the sample. Furthermore, the collected data was analyzed descriptively-qualitatively so that the values ​​of ecological preaching that had been implemented were identified and the form and process of implementation by the Matras Tourism Village community. The findings show that there are five types of ecological preaching values ​​that have been implemented, namely al-Is (justice), al-Tawazun (balance), al-Intifa 'wa laa al-Fasad (taking benefits without damage), ar-Riayah wa laa al -Israf (nurturing without exaggeration), and al-Tahdits wa al-Istikhlaf (renewal). Unfortunately, the value of al-Tahdits wa al-Istikhlaf is still not optimal due to the quality of science and technology. However, the local community has become more aware and intelligent about the importance of ecological preaching values ​​in the development of Mattress Tourism Village. In the future, besides needing to intensify and harmonize the role of ulama and Umara, it must also be carried out to increase the capacity of religious institutions, knowledge and appropriate technology for program implementers, and to involve community participation in planning, implementing and evaluating the Matras Tourism Village development program.